Implementation of Discovery Learning Model with Window Shopping Approach to Improve Mathematical Communication Ability of High School Students - Rahman, Andi; Putra, Harry; Hendriana, Heris ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
The low ability of students' mathematical communication in learning mathematics, especially in expressing mathematical situations or problems in the form of pictures, diagrams, language or mathematical symbols, or mathematical models makes students less active in learning and their learning motivation decreases. This study aims to determine the achievement of students' mathematical communication skills through the discovery learning model with a window shopping approach. The method in this study is a quasi-experimental research type consisting of 2 classes, namely the experimental class that uses the discovery learning model with the window shopping approach and the control class that uses ordinary learning at school with a total of 70 students from class XI SMA in one of the public high schools in Bandung. The research test instrument was in the form of a test that would be analyzed using SPSS 21 to compare learning outcomes between the experimental class and the control class. The result of the study was that the achievement of the students' mathematical communication skills in the experimental class was better than that of the control class at a significance level of 0.05 where the average communication ability of the experimental class was 81.74 and that of the control class was 77.31. The effectiveness of learning in the experimental class showed that it was more active in group discussions as indicated by the interaction and creativity of students in presenting learning material in each group, and almost 85% of students enjoyed learning using the discovery learning model with the window shopping approach.